The analysis of thermal performance of radiation life support system based on experimental data - V. I. Karagusov; A. V. Zinovieva (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
Solar energy is considered a renewable, most environmentally friendly and carbon-free form of energy. Solar collectors are one of the implementations of radiation life support systems. Their development requires a fairly large amount of initial data, such as the parameters of the premises, the required temperature, volume, thermal insulation of walls, floors and ceilings, the design of windows and doors, orientation to the cardinal points, the angles of inclination of the roof slopes, etc. The next group of factors is related to the location object, latitude, altitude above sea level, distance to large bodies of water, wind rose, etc. The third group is related to the weather itself: precipitation, cloudiness, outside air temperature, etc., a significant part of them, such as fog, haze, dew, shadow from each cloud affects the amount of insolation and all this cannot be taken into account in advance. The use of weather archives does not allow us to fully determine the specific thermal performance of solar collectors, since neither the average nor the current insolation is reflected in the archives. Without knowing the amount of real insolation and heat losses on the solar collector, it is impossible to determine the thermal performance of the radiation life support system per day, month, season or year. This paper discusses experimental and computational studies of the radiation life support system carried out in 2018–2022.